SECONDARY METABOLITES AND BIOLOGICAL PROFILES OF DATURA GENUS - Céspedes, Camilo (Journal of the Chilean Chemical Society, 2021)
Solanaceae is an important family of plants where many species of this family are source for food, industrial products, ornamental and medicinal uses. Within the family of Solanaceae, the genus Datura is one of the most interesting, in principle for its known medicinal and psychotropic uses against different pathologies. Multiple biological activities of Datura species have been documented. The species of the genus are attributed with insecticide, fungicide, antioxidant, antimicrobial, hypoglycemic, and immune response enhancing activity against cancer cells. These activities are related to the presence of different secondary metabolites such us: terpenoids, flavonoids, withanolides, tannins, phenolic compounds and tropane alkaloids, the main secondary metabolite of the genus Datura, being the most abundant atropine and scopolamine. The propose of this review is to identify the main phytochemical compounds isolated from the genus Datura and describe their biological activities associated to different secondary metabolites.